Composition and Diversity of Trammel net Catches Landed at PPI Cikidang, Pangandaran - Pratama, Gilar Budi; Baihaqi, Faqih; Sri Wijayanti, Lady Ayu; Muhyun, Ainun Apriliyani (Jurnal Perikanan Terpadu, 2025)
Fishing activities are one of the main economic supports for coastal communities in Pangandaran, especially at the Cikidang Fish Landing Base (PPI Cikidang). Trammel nets are widely used, but the impact on the composition and diversity of the catch is not well understood. This study aims to analyze the dynamics of production, CPUE (Catch per Unit Effort) values, composition, and diversity of trammel net catches from 2019 to 2021. Secondary data from PPI Cikidang were analyzed descriptively and quantitatively, using trend graphs, frequency distribution, CPUE, and the Shannon-Wiener diversity index (H'). The results showed that production and fishing efforts fluctuated seasonally, peaking in mid- to late years. The highest CPUE value occurred in October 2020 at 39.19 kg/trip, while the lowest value was recorded in April 2021 at 14.17 kg/trip. The catch composition was dominated by shrimp, particularly Dogol Shrimp (Metapenaeus monoceros), which increased from 50.61% (2019) to 60.55% (2021). The diversity index showed a decline from 1.50 (2019) to 1.08 (2021), indicating the dominance of certain species and the potential decline in ecosystem stability. These findings highlight the importance of sustainable management of trammel net fishing gear to prevent negative impacts on marine biodiversity in the area